Scientifically Unaccepted Beliefs on Traditional Health Care Using Energy Techniques - Reyhan Kama, A. S.; Rossalina, Lolla; Nugroho, Syaifudin (International Journal of Social Science, Education, Communication and Economics, 2024)
Practices that use methods that are not scientifically acceptable, such as psychics and traditional health services, are part of cultures in various parts of the world, tribes, races, and throughout the history of human civilization until now. This research uses a qualitative, phenomenological approach, which is based on the theory of "Scientifically Unaccepted Beliefs" developed by Harvey Irwin. The data collection process was carried out by interviewing individuals who were practitioners of traditional health using energy techniques. Authentication regarding participant practices is carried out by documenting official letters from the government of the Republic of Indonesia that acknowledge these practices. Based on data analysis carried out on the results of interviews with two participants, it is known that there are unique aspects in their lives that support the formation of beliefs about things that cannot be accepted scientifically. The research results also found that each participant had a certain motivation to carry out each service practice using methods that were not scientifically acceptable.